2013
DOI: 10.1103/physrevlett.110.064501
|View full text |Cite
|
Sign up to set email alerts
|

Real-Space Manifestations of Bottlenecks in Turbulence Spectra

Abstract: An energy-spectrum bottleneck, a bump in the turbulence spectrum between the inertial and dissipation ranges, is shown to occur in the non-turbulent, one-dimensional, hyperviscous Burgers equation and found to be the Fourier-space signature of oscillations in the real-space velocity, which are explained by boundary-layer-expansion techniques. Pseudospectral simulations are used to show that such oscillations occur in velocity correlation functions in one-and three-dimensional hyperviscous hydrodynamical equati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 31 publications
(23 reference statements)
1
28
0
Order By: Relevance
“…The initial condition IC2 is like IC1 but, in addition, it has a finite initial condensate population N i 0 =|ψ(k = 0, t) | 2 ( k) 2 at time t = 0. Note the study of [41] uses a hyper-viscosity term ν(−∇ 2 ) n ψ, which is absent in our study; such hyperviscosity terms can modify energy spectra in important ways, as has been discussed in the context of turbulence in the Navier-Stokes equation in [50,63].…”
Section: Numerical Methods and Initial Conditionsmentioning
confidence: 99%
“…The initial condition IC2 is like IC1 but, in addition, it has a finite initial condensate population N i 0 =|ψ(k = 0, t) | 2 ( k) 2 at time t = 0. Note the study of [41] uses a hyper-viscosity term ν(−∇ 2 ) n ψ, which is absent in our study; such hyperviscosity terms can modify energy spectra in important ways, as has been discussed in the context of turbulence in the Navier-Stokes equation in [50,63].…”
Section: Numerical Methods and Initial Conditionsmentioning
confidence: 99%
“…Specifically, equipartition solutions to the Galerkin-truncated Gross-Pitaevskii [19], magnetohydrodynamic [20], Burgers [5,17], and Euler equations [6,21] have been studied extensively in recent years. Alongside the very important theoretical under-pinnings of such studies, thermalised or partially thermalised states have been shown [22][23][24] to be a possible explanation of the ubiquitous bottleneck [25] in the energy spectrum of turbulent flows.…”
Section: Introductionmentioning
confidence: 99%
“…When this expression is converted to the spectral domain, it recovers the spectral bottleneck reported at the crossover from inertial to dissipation (Katul et al, ). This bottleneck is commonly identified by a bump when the compensated spectrum k 5/3 E w w ( k ) is plotted against k in the vicinity of k η ≈0.1 and has been the subject of active research (Davidson, ; Dobler et al, ; Donzis & Sreenivasan, ; Frisch et al, , ; Herring et al, ; Hill, ; Katul et al, ; Meyers & Meneveau, ). The assumed spectrum by Lamont and Scott () exhibits an inertial subrange adjusted with a power‐law viscous cutoff based on the Kovasznay spectrum.…”
Section: Theorymentioning
confidence: 99%